The Effect Of Structural Analytic Synthetic (Sas) Method Using Word Card Learning Media On The Initial Reading Skills Of Grade 1 Students - kawanti, anidia; Hamzah, Rahma Ashari; Setiawan, Ince Prabu (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
The problem in this study is the low reading skills of students, where students sometimes forget to remember letters, students sometimes forget to connect words, and there are still students who stammer in spelling a reading. This research aims to find out: 1) an overview of the application of the Structural Analytic Synthetic (SAS) method using word card learning media to the beginning reading skills of grade 1 students of SDN 99 Kadieng Maros Regency; 2) the effect of the Structural Analytic Synthetic (SAS) method using word card learning media on the beginning reading skills of grade 1 students of SDN 99 Kadieng Maros Regency. This research is an experimental research with the type of research is pre-experimental design in the form of one group pretest-posttest design. The data collection techniques used were observation, reading tests, and documentation. The data analysis techniques used were descriptive and inferential analysis. The results showed that: 1) the description of the application of the Structural Analytic Synthetic (SAS) method using word card learning media took place very well, because the percentage category for each meeting had changes seen from teacher and student observations; 2) the results of descriptive and inferential analyses obtained from the results of reading tests in the from of pretests and posttests that have been carried out, it can be concluded that the application of the Structural Analytic Synthetic (SAS) method using word card learning media has an influence on the beginning reading skills of grade 1 students. This can be seen from the results of hypothesis testing with a significance value of 0.000 < 0.05.